MKL1 Mediates TGF-β Induced RhoJ Transcription to Promote Breast Cancer Cell Migration and Invasion - Chen, Baoyu; Yuan, Yibiao; Sun, Lina; Chen, Junliang; Yang, Mengzhu; Yin, Yongmei; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Differential regulation of gene transcription contributes to cancer metastasis. We investigated the involvement of a small G-protein (RhoJ) in breast cancer metastasis focusing on the mechanism underlying RhoJ trans-activation by pro-metastatic cues. We report that expression of RhoJ was up-regulated in malignant breast cancer cells compared to more benign ones. Higher RhoJ expression was also detected in human breast cancer biopsy specimens of advanced stages. RhoJ depletion attenuated breast cancer cell migration and invasion in vitro and metastasis in vivo. The pro-metastatic stimulus TGF-b activated RhoJ via megakaryocytic leukemia 1 (MKL1). MKL1 interacted with and was recruited by ETS-related gene 1 (ERG1) to the RhoJ promoter to activate transcription. In conclusion, our data delineate a novel transcriptional pathway that contributes to breast cancer metastasis. Targeting the ERG1-MKL1-RhoJ axis may be considered as a reasonable approach to treat malignant breast cancer.